2014
DOI: 10.1111/rda.12350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Three pFSH Doses on Superovulation and Embryo Quality in Goats During Two Breeding Seasons in North‐eastern Mexico

Abstract: The aim of this research was to evaluate the effectiveness of three pFSH doses (80 mg; 145 mg and 215 mg) on ovarian response and on quantity and quality of transferable embryos of goats during the breeding and the non-breeding seasons. Ovary structures were exposed (laparatomy under general anaesthesia) and numbers of follicles and corpora lutea were registered. Surgical embryo flushing was conducted to count and classify embryos. There were more follicles (3.4 ± 1.1) in does administered 80 mg of pFSH (p < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
3
9
0
Order By: Relevance
“…Brasil et al () observed a similar number of CLs to that obtained in this study using 133 mg of total dose of pFSH in Santa Inês ewes. Sanchez‐Dávila et al () reported similar number of CLs in response to 145 and 215 mg of total dose of pFSH for superovulation in goats whereas lower ovarian response was recorded when 80 mg was used; the same was recorded to produce transferable embryos. The number of CLs observed in this experiment was greater than observed by Oliveira et al () with the same protocol of superovulation in Santa Inês ewes using 200 mg of total dose of pFSH.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Brasil et al () observed a similar number of CLs to that obtained in this study using 133 mg of total dose of pFSH in Santa Inês ewes. Sanchez‐Dávila et al () reported similar number of CLs in response to 145 and 215 mg of total dose of pFSH for superovulation in goats whereas lower ovarian response was recorded when 80 mg was used; the same was recorded to produce transferable embryos. The number of CLs observed in this experiment was greater than observed by Oliveira et al () with the same protocol of superovulation in Santa Inês ewes using 200 mg of total dose of pFSH.…”
Section: Discussionmentioning
confidence: 96%
“…In small ruminants superovulatory protocols, the total doses of pFSH (Folltropin®, Bioniche, Canada) more frequently used are 256 mg (Oliveira et al, ), 215 mg (Sánchez‐Dávila et al, ) or 200 mg (Loiola Filho et al, ; Oliveira et al, ) while in cows good results are achieved with lower doses (100–133 mg) (Baruselli et al, ). Therefore, studies addressing the efficacy of lower doses of FSH in sheep are needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that glucose participates in the control of ovarian function, where the levels are regulated by insulin, which plays an important role in follicular growth in goats [35].…”
Section: Nutrition and Body Conditionmentioning
confidence: 99%
“…It has been evaluated that the goats must maintain a body condition of 3 so that the reproduction is not affected negatively; here, the visual aspect of the goat would be the backbone is not prominent, ribs are barely discernible, and an even layer of fat covers them. Intercostal spaces are felt using pressure [35].…”
Section: Nutrition and Body Conditionmentioning
confidence: 99%